Exploring disparities and novel insights into metabolic and cardiovascular comorbidities among COVID-19 patients in Mexico - Jonathan Ariel López-Cuevas; Jonathan Ariel López-Cuevas; Mireya Martínez-García; Enrique Hernández-Lemus; Enrique Hernández-Lemus; Guillermo de Anda-Jáuregui; Guillermo de Anda-Jáuregui; Guillermo de Anda-Jáuregui (Frontiers Media S.A., 2023)
IntroductionThe COVID-19 pandemic, especially its early stages, sparked extensive discussions regarding the potential impact of metabolic and cardiovascular comorbidities on the severity and fatality of SARS-CoV-2 infection, yielding inconclusive outcomes. In this study, we delve into the prevalence of metabolic and cardiovascular comorbidities within COVID-19 patients in Mexico.MethodsEmploying a retrospective observational study design, we collected data from official databases encompassing COVID-19 patients admitted to both public and private hospitals in Mexico City.ResultsOur investigation unveiled a noteworthy incongruity in the prevalence of metabolic and cardiovascular comorbidities among COVID-19 patients, with a particular emphasis on obesity, hypertension, and diabetes. This incongruity manifests as location-dependent phenomena, where the prevalence of these comorbidities among COVID-19 patients significantly deviates from the reported values for the general population in each specific location.DiscussionThese findings underscore the critical importance of screening for metabolic and cardiovascular comorbidities in COVID-19 patients and advocate for the necessity of tailored interventions for this specific population. Furthermore, our study offers insights into the intricate interplay between COVID-19 and metabolic and cardiovascular comorbidities, serving as a valuable foundation for future research endeavors and informing clinical practice.